Ohtrasti ohte - Santeri Junttila (Keel ja Kirjandus, 2023)
The dictionary of Estonian dialects (EMS) lists oht as three lexical items: oht1 (= South Estonian oht) ‘1 peril, danger, menace; jeopardy, risk, hazard; 2 distress’; oht2 ‘(herbal) medicine, drug, antidote’; and the partitive-only ohtu ‘-like, -ish, resembling, as good as’. Mägiste (1929) has connected oht1 to Votic and Ingrian ohto ‘enough’ and further with Estonian oher (in literary language ohter) ‘abundant, plentiful; liberal, bountiful; rich; opulent; profuse’, explaining the meaning ‘distress’ as derived from ‘abundance of distress’.